Outcome and cervical metastatic spread of squamous cell cancer of the buccal mucosa, a retrospective analysis of the past 25 years. (6th June 2017) - Sagheb, Keyvan; Blatt, Sebastian; Kraft, Ina Sophie; Zimmer, Stefanie; Rahimi‐Nedjat, Roman‐Kia; Al‐Nawas, Bilal; Walter, Christian
Abstract : Objectives: Because of the low proportion of squamous cell carcinomas (SCCs) of the buccal mucosa within the carcinomas of the oral cavity in the Western population, data concerning metastatic pattern are sparse. Therefore, this retrospective study is focusing on the occurrence of cervical metastases (CM) and the overall outcome of this tumor entity. Materials and Methods: From January 1988 to October 2013, 113 patients were treated in the Department of Oral and Maxillofacial Surgery, Mainz, for an oral SCC of the cheek. Metastatic pattern and clinical parameters that are possibly associated with an increased risk for CM as well as overall outcome were analyzed. Results: The average follow‐up was 48 months (range: 1–248 months). A total of 55 (49%) patients were female and 58 (51%) male, with an average age of 65 ± 13 years (♀68 ± 14 years; ♂63 ± 11 years). In total, 55% of the patients either smoked and/or consumed alcohol. In total, 34% of the patients had a stage III or IV tumor, with overall 23% having CM at the time of diagnosis. During the follow‐up, 50% ( n = 56) of the patients developed a relapse after 12 months (median). Tumor size ( P = 0.002*) and grading ( P < 0.001*) are significantly associated with the occurrence of CM. Metastases ( P = 0.008*) and advanced tumor size ( P = 0.018) had an influence on the survival, whereas the relapse had no significant influence ( P = 0.928). Five‐year survival rate was 80%. Conclusions: SCC of the buccal mucosa shows aggressive behavior with a considerably high proportion of relapse. Since overall outcome is significantly decreased by the cervical metastatic pattern, a selective, ipsilateral neck dissection for this patient group is recommended as the primary management.